Viabilidade agroeconômica de associações de cultivares de caupi- hortaliça com cultivares de beterraba adubadas com flor-de-seda - Ribeiro, Jeisy Rafaela de Souza (2018)
The objective of this work was to evaluate the agroeconomic performance of associations of cowpea-vegetable cultivars with beet cultivars fertilized with Calotropis procera. The experiment was conducted at the Rafael Fernandes Experimental Farm, Alagoinha, Mossoró-RN, between August and November 2016. The experimental design was of randomized complete blocks, with the treatments arranged in a 4 x 2 factorial scheme with 4 replications. Single plots of each cultivar were planted in each block to obtaining the agro-economic efficiency indices of the intercropped systems. The treatments consisted of the combination of four cultivars of cowpea-vegetable (BRS Tumucumaque, BRS Cauamé, BRS Guariba and BRS Itaim) with two cultivars of beet (Early Wonder and Fortuna). The characteristics evaluated in the cowpea-vegetable were: green pod length, number of green pods per area, productivity and dry mass of green pods, number of green grains per pod, and productivity and dry mass of green grains. In the beet crop were: plant height, diameter of roots, fresh and dry mass of shoots and dry mass of roots, productivities total, commercial and classified of roots. The agro-economic indices determined were: land equivalent ratio, productive efficiency index, score of the canonical variable (Z), aggressivity, competitive ratio, gross income, net income, rate of return and profit margin. Univariate analyzes of variance for the randomized complete block design were performed on the crop variables and on the agro-economic indices of the intercropped systems. A multivariate analysis of variance was also performed on crop yields to obtaining of the score of the canonical variable (Z) as a function of treatment factors. The greater agro-economic efficiency of the intercropping system of cowpea-vegetable and beet was obtained with the combination of the cultivar of cowpea-vegetable BRS Guariba with the beet cultivar Early Wonder. The beet was the dominant culture and the cowpea-vegetable the culture dominated in the intercropped system. The intercropping system of beet with cowpea-vegetable produced 60.5% of the total productivity and 56.6% of the productivity of commercial roots in relation to beet monoculture